Long-term mortality following interhospital transfer for acute myocardial infarction. Issue 13 (3rd March 2015) - Ranasinghe, Isuru; Barzi, Federica; Brieger, David; Gallagher, Martin
Abstract : Background: Interhospital transfer of patients admitted with an acute myocardial infarction for specialised care is common and costly. However, the long-term mortality of transferred patients compared with patients solely treated at the presenting hospital has not been evaluated. Here, we assess the long-term mortality of patients who undergo interhospital transfer during their acute myocardial infarction admission. Methods: We evaluated 40 482 patients with a ICD10-AM diagnosis of acute myocardial infarction admitted to hospitals in New South Wales, Australia, from 2004 to 2008, of whom 10 107 (25%) were transferred. We compared in-hospital and mortality up to 5.5 years postdischarge among transferred and non-transferred patients. We created a 1:1 propensity score matched cohort (n=16 854; 8427 per group) to account for selection bias. Results: In the matched cohort, transferred patients were more likely to undergo revascularisation (55.6% vs 13.7%, RR 4.05; 95% CI 3.83 to 4.29) and had lower mortality at 30 days (3.5% vs 5.7%, HR 0.60; 95% CI 0.52 to 0.70), 1 year (7.5% vs 12.6%, HR 0.58; 95% CI 0.52 to 0.64) and at the end of follow-up (15.3% vs 22.5%, HR 0.65; 95% CI 0.61 to 0.70) than patients treated in presenting hospitals. With the exception of transfers originating from revascularisation capable hospitals, these findings were consistent across a range of subgroups, including patients of all ages, ST-elevation myocardial infarction and non ST-elevation myocardial infarction patients, and transfers originating from hospitals in regional and major city areas. Sensitivity analyses showed that these findings are unlikely to be due to survival bias or to confounding by unmeasured variables. Conclusions: Patients hospitalised for an acute myocardial infarction who are transferred to one or more hospitals for specialised care have higher rates of coronary revascularisation and experience lower long-term mortality.